2021
DOI: 10.2967/jnumed.120.257279
|View full text |Cite
|
Sign up to set email alerts
|

Improved Primary Staging of Marginal-Zone Lymphoma by Addition of CXCR4-Directed PET/CT

Abstract: Positron emission tomography/computed tomography (PET/CT) with 18 Ffluorodesoxyglucose (FDG) is an integral component in the primary staging of most lymphomas. However, its utility is limited in marginal zone lymphoma (MZL) due to inconsistent FDG avidity. One diagnostic alternative could be the targeting of CXC-motif chemokine receptor 4 (CXCR4), shown to be expressed by MZL cells. This study investigated the value of adding CXCR4-directed 68 Ga-Pentixafor PET/CT (CXCR4 PET/CT) to conventional staging. Method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
52
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

5
5

Authors

Journals

citations
Cited by 48 publications
(56 citation statements)
references
References 22 publications
0
52
0
4
Order By: Relevance
“…Additionally, CXCR4 has recently emerged as an interesting molecular target in marginal zone lymphoma [ 14 , 15 ], gastric mucosa-associated lymphoid tissue (MALT) lymphoma [ 16 ], mantle cell lymphoma [ 17 ], myeloproliferative neoplasms [ 18 ] as well as primary lymphoma of the central nervous system [ 19 ]. In Waldenström macroglobulinemia/lymphoplasmacytic lymphoma, a disease in which about 40% of patients have mutations in the CXCR4 gene, preliminary results with non-invasive PET imaging using [ 68 Ga]Pentixafor have demonstrated promising results in both staging and therapy response assessment.…”
Section: Cxcr4-targeted Theranostics In Cancer and Its Limitationsmentioning
confidence: 99%
“…Additionally, CXCR4 has recently emerged as an interesting molecular target in marginal zone lymphoma [ 14 , 15 ], gastric mucosa-associated lymphoid tissue (MALT) lymphoma [ 16 ], mantle cell lymphoma [ 17 ], myeloproliferative neoplasms [ 18 ] as well as primary lymphoma of the central nervous system [ 19 ]. In Waldenström macroglobulinemia/lymphoplasmacytic lymphoma, a disease in which about 40% of patients have mutations in the CXCR4 gene, preliminary results with non-invasive PET imaging using [ 68 Ga]Pentixafor have demonstrated promising results in both staging and therapy response assessment.…”
Section: Cxcr4-targeted Theranostics In Cancer and Its Limitationsmentioning
confidence: 99%
“…This transmembrane receptor is involved in the cell migration process and in the homing of hematopoietic stem cells to the bone marrow compartment. Several studies reported the use of 68Ga-Pentixafor that showed a high contrast in CXCR4-expressing lymphomas [114][115][116][117]. Furthermore, for a theranostic approach, its therapeutic properties are currently under investigation, radiolabeled with βor α-emitters [118].…”
Section: Phenotypic Imagingmentioning
confidence: 99%
“…Patients fasted at least 6 h prior to injection of 289.1 ± 38.5 MBq [ 18 F]FDG. PET/CT scans were acquired after 60 min post-injection, using non-contrast-enhanced CT with CARE Dose 4D with the following parameters: 160 mAs, 120 kV, 512 × 512 matrix, 5 mm slice thickness, slice collimation 64 × 0.6 mm [13]. PET data were reconstructed according to standard protocols as described in [13].…”
Section: Pet/ct Acquisitionmentioning
confidence: 99%